2013
DOI: 10.1007/s13197-013-1230-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing biochemical changes during standardization of fermentation time and temperature for manufacturing quality black tea

Abstract: In black tea manufacturing, one of the most important steps is fermentation which influences the quality of tea. The macerated tea leaves were fermented at various temperatures (20, 25, 30, 35 °C) for different duration. Changes in polyphenoloxidase and peroxidase activities, depletion patterns of individual catechins, differences in individual theaflavin levels and formation of thearubigins were measured in leaves during fermentation. Higher stability of polyphenoloxidase and peroxidase enzymes was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…Figures and show the effect of temperature and bed thickness on depletion of catechins (EGCG, ECG, EGC, and EC) during oxidation of CTC and orthodox leaves. The rates of catechin oxidation increased with the increase in air temperature, may be due to higher activity of PPO and PO at high temperature, as reported by Samanta et al (). Amount of EGCG is maximum in green leaf (nonoxidized sample) of TV25 clone, followed by EGC, ECG, and EC.…”
Section: Resultssupporting
confidence: 70%
“…Figures and show the effect of temperature and bed thickness on depletion of catechins (EGCG, ECG, EGC, and EC) during oxidation of CTC and orthodox leaves. The rates of catechin oxidation increased with the increase in air temperature, may be due to higher activity of PPO and PO at high temperature, as reported by Samanta et al (). Amount of EGCG is maximum in green leaf (nonoxidized sample) of TV25 clone, followed by EGC, ECG, and EC.…”
Section: Resultssupporting
confidence: 70%
“…On the other hand, these enzymes are desirable in the process of black tea production, and can catalyse the transformation of catechin to thea avins (TF) and thearubigins (TR), responsible for the typical avour and colour of black tea [Jiang 2008]. The roles of PPO and PO in transforming catechin compounds to TF and TR have also been highlighted, and this has direct bearing on the quality of black tea [Samanta et al 2015]. Both of the oxidative enzymes PPO and POD are of considerable importance in black tea processing and for the quality and avour of the tea.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [18] reported that with increase in temperature, the stability of enzyme decreased during fermentation and at 35 °C it can only be observed 90% stability of polyphenoloxidase up to 40 min. This decrease in polyphenoloxidase activity during fermentation could explain the increase in total phenolics content observed after fermentation beyond 38 °C for more than 1 h since polyphenoloxidase oxidizes the phenolic compounds.…”
Section: Response Surface Methodologymentioning
confidence: 99%